2018
DOI: 10.1016/s0140-6736(18)30021-7
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of NaV1.4, a skeletal muscle voltage-gated sodium channel, in sudden infant death syndrome: a case-control study

Abstract: SummaryBackgroundSudden infant death syndrome (SIDS) is the leading cause of post-neonatal infant death in high-income countries. Central respiratory system dysfunction seems to contribute to these deaths. Excitation that drives contraction of skeletal respiratory muscles is controlled by the sodium channel NaV1.4, which is encoded by the gene SCN4A. Variants in NaV1.4 that directly alter skeletal muscle excitability can cause myotonia, periodic paralysis, congenital myopathy, and myasthenic syndrome. SCN4A va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 45 publications
1
60
1
Order By: Relevance
“…Patient II‐a demonstrated repeated episodes of rhabdomyolysis that were induced by swimming or traumatic injury, which indicated that her myotonia was very severe. Laryngospasm, a symptom observed in patient II‐b who carried E1702K, could be related to SIDS . On the other hand, a previous clinical report of the E1702K mutation showed milder symptoms than those in our cases .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Patient II‐a demonstrated repeated episodes of rhabdomyolysis that were induced by swimming or traumatic injury, which indicated that her myotonia was very severe. Laryngospasm, a symptom observed in patient II‐b who carried E1702K, could be related to SIDS . On the other hand, a previous clinical report of the E1702K mutation showed milder symptoms than those in our cases .…”
Section: Discussioncontrasting
confidence: 63%
“…Importantly, SCN4A variants have also been found in infant cases of life‐threatening apnea and laryngospasm, or so‐called “severe neonatal episodic laryngospasm (SNEL)” . The severe apnea and laryngospasm can be a contributing factor in sudden infant death syndrome (SIDS), which is the leading cause of postneonatal infant death in high‐income countries …”
Section: Introductionmentioning
confidence: 99%
“…We recently described a similar gain-of-function mutation in sudden infant death, 8 and such mutations are a recognized cause of recurrent life-threatening apneas in infants with myotonia and laryngospasm. 4,5 In children with the latter, there is clear evidence that the muscle phenotype evolves with age; that is, apneas are prominent and symptomatic in early life but diminish with age.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, for one of the "other neurological genes", SCN4A, we recently demonstrated a significant (p= 0.0057) overrepresentation of functionally disruptive variants in European SIDS versus ethnic-matched controls. 33 The SCN4A encoded skeletal muscle voltage-gated sodium channel (Nav1.4)…”
Section: Discussionmentioning
confidence: 99%